Integration of Training and Retention in Improving Employee Well-being through Competency Mediation in the Banking Sector - Siti Rohani; Cellina Tan; Ratih Anggraini (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study examined the effects of employee retention, human resource development, and career satisfaction on employee well-being, with competence as a mediating variable. Methodology/approach: This quantitative research used the Partial Least Squares – Structural Equation Modeling (PLS-SEM) method with SmartPLS software. Data were collected via a Likert-scale questionnaire from 277 banking employees in Batam who had participated in training programs. Results: Employee retention, HR development, and career satisfaction significantly influence competence, which in turn significantly impacts employee well-being. These three independent variables also affect well-being indirectly through competence mediation. The R-square values (0.942 and 0.915) and a goodness-of-fit index of 0.797 demonstrate strong model predictive power. Conclusions: Improving employee well-being should focus on strengthening employee competence through consistent retention strategies, structured training programs, and clear career development pathways. Limitations: This study is limited by its focus on employees in the banking sector in Batam, which may not fully represent all industries or regions. Contributions: This study integrates three key HR factors in a single model and positions competence as a mediator in the banking sector, a topic that has been underexplored in Indonesian settings.